Markerless video-based estimation of 3D approach velocity in the javelin throw - Köykkä, M.; Vohlakari, K.; Joutsen, T.; Vänttinen, T.; Piironen, P.; Rantalainen, T.; Cronin, N. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to explore the usefulness of a markerless open-source human pose estimation algorithm, for estimating centre of mass (CoM) velocity in the javelin throw at three discrete time instances: the last right leg touchdown (RLTD), brace leg touchdown (BLTD) and release. Forty throws from four right-handed javelin throwers were simultaneously captured with two high-speed video cameras and a 16-camera marker-based Vicon motion capture system. For horizontal resultant velocity (Vel_hor), the method demonstrated excellent validity at RLTD, whereas at BLTD and release errors were notable. Based on these findings, CoM Vel_hor can be estimated using the proposed method with promising accuracy at RLTD. At BLTD and release, using a CoM segment model with arms in more optimized measurement conditions might further improve the accuracy.